Study of dopant redistribution during gate oxide breakdown in narrow MOSFETs - Lim, Wai Tat. (2008)
The purpose of this project is to study the dopant redistribution and its associated effect on the diode I-V characteristics of the source and drain during gate oxide breakdown in narrow metal-oxide-semiconductor field-effect transistor (MOSFET). During the evolution of gate dielectric progressive breakdown, the substantially high localized temperatures in the vicinity of the breakdown spot which can exceed silicon melting point will cause impurity dopants in the silicon to be redistributed.